(untitled) (Islamic Sciences Journal, 2023)
When you read and write about a critical study, you must take into account the impartiality and objectivity, whether this study may have a negative or a positive side, and it is not correct to assert the results of that study. The academic criticism is to re-imagine the perception and understanding of the written text that the study underwent. So it is the process of showing the errors and advantages of literary studies because of the methods, ideas and perceptions it contains. My study was entitled (The Method of Interpretation by the Neglected Letters for Hamzawi in his Interpretation of Dar Al-Asrar) (a critical study), as the researcher wanted to clarify the new method in which the author worked, by studying these perceptions and ideas ,in a critical study, showing whether the author was able to succeed and excel, with this kind of Interpretation, or not, through the tools of constructive academic criticism.